Lacrimal drainage anomalies in congenital rubella syndrome - Gupta S (Dove Medical Press, 2017)
Shweta Gupta, Mohammad Javed Ali, Milind N Naik Govindram Seksaria Institute of Dacryology, L. V. Prasad Eye Institute, Hyderabad, India Purpose: The objective of this study was to ascertain the lacrimal drainage anomalies in a cohort of patients suffering from congenital rubella syndrome (CRS).Methods: This was a retrospective case series performed in patients with CRS presenting with associated lacrimal drainage anomalies (LDA) over 6 years from 2011 to 2016. All the patients were confirmed as having CRS after clinical and laboratory testing. Data collected include demographics; associated lacrimal, ocular, and systemic anomalies; interventions performed for lacrimal anomalies; and their anatomical and functional outcomes.Results: Eighty five patients were diagnosed as having CRS during the study period, and of these 23 eyes of 12 patients with associated LDA were included in the study. The prevalence of LDA was 14% in CRS. The mean age at presentation was 15.5 weeks, and all except one had bilateral presentation. Seventeen eyes were diagnosed with simple congenital nasolacrimal duct obstruction (CNLDO) and the remaining six eyes had complex CNLDO with buried probes. Additional lacrimal anomalies noted in the six complex CNLDO cases included punctal agenesis (n=3), atonic sac (n=3), incomplete punctal canalization (n=2), and single canalicular wall hypoplasia (n=1). At a mean follow-up of 12.54 months, anatomical and functional success were noted in 91.3% (21/23 eyes).Conclusion: Simple CNLDO was the most common of the LDA in CRS. Buried probe was universal among the cases with complex CNLDO. All CRS patients should be screened for lacrimal anomalies to initiate appropriate interventions for successful outcomes. Keywords: rubella, lacrimal drainage, CNLDO, buried probe, punctal agenesis